Krzysztof Nawotka, The Nourisher of Apollo. - Huy , Sabine (Journal of Greek Archaeology, 2024)
The polis Miletos, praised by Herodot (V 28,1) as the “ornament of Ionia”, is especially acknowledged for its political role in Archaic times. In this period, it is known as the founder of numerous colonies along the coasts of the Black Sea area, as well as the birthplace of Ionian philosophy (“Ionian Enlightenment”). It was a centre of extensive art and craft production and home of the renowned sanctuary of Apollo and his oracle at Didyma. The period of prosperity came to a harsh end when, in 494 BCE, Miletos and its territory were devastated by the Persians to put an end to the Ionian revolt – and this is where research on Miletos usually fades out. In over 100 years, the post-Archaic phases of Miletos have been the subject of only selective studies.